Uji Daya Hambat Isolat Bakteri Asam Laktat Usus Itik (Anas Domestica) Pada Bakteri Gram Positif Dan Pola Pertumbuhan Isolat Bakteri Usus Itik Pada Media Mrs Broth - Rudy Sutrisna; Nugroho Ekowati; Diah Rahmawati (Politeknik Negeri Lampung., 2013)
At this time unknown bacterial isolates inhibit the ability of the isolated intestine of ducks against Gram-positive bacteria such as Bacillus subtilis and Staphylococcus aureus. In addition, the growth pattern is also unknown bacterial isolates grew on the medium MRS Broth. This study aims to determine the inhibition of intestinal bacterial isolates antibacterial extract of duck against Gram-positive bacteria and determine the pattern of growth of intestinal bacteria duck isolates were selected on MRS Broth media. Determination of the inhibition assay duck intestine bacterial isolates using the wells, while for the determination of growth patterns of duck intestine bacterial isolates by counting directly the number of bacterial cells by microscopy. The results showed that the bacterial isolates capable of inhibiting the growth of colon duck Gram-positive bacteria. Isolates that produce the greatest diameter of the results of this research that isolates B4 and B9 at 20.2 mm and 17.9 mm long production time 4 days. Growth of intestinal bacteria isolates duck B4 shows the phase lag for 2 hours and logarithmic phase for 17 hours, while isobat B9 shows the phase lag for 3 hours and logarithmic phase for 10 hours. Keywords: Intestinal Bacterial Isolates Ducks, Inhibition Power Test, Growth Patterns, Staphylococcus aureus, and Bacillus subtilis